The Influence of Viral Marketing at Tiktok and Ticket Prices on Tourists’ Decision to Visit Maimun Palace in Medan City - Fauzia, Dila Latul; Adlina, Hafiza (PT FORMOSA CENDEKIA GLOBAL, 2024)
Wider dissemination of information and setting relatively affordable ticket prices through the TikTok application will be able to increase tourists' visiting decisions. This examination means to quantify the impact of viral marketing on TikTok and ticket costs on travelers' choices to visit Maimun Palace In the city oF Medan. This exploration utilizes quantitatIve techniques with an affiliated methodology. . This research uses various tests using SPSS software to obtain research results, namely validity test, reliability test, classical assumption test, multiple linear regression analysis, hypothesis testing (t test, f test, and R2 test). Based on the results of SPSs data processing, the results/findings of viral marketing and the price of entrance tickets have a positive and significant influence partially and simultaneously on variable Y, namely the decision of tourists to visit Maimun Palace, Medan City.